Development of an ultra-sensitive Simoa assay to enable GDF11 detection: a comparison across bioanalytical platforms. (March 2016) - Myzithras, Maria; Li, Hua; Bigwarfe, Tammy; Waltz, Erica; Gupta, Priyanka; Low, Sarah; Hayes, David B; MacDonnell, Scott; Ahlberg, Jennifer; Franti, Michael; Roberts, Simon
Background: Four bioanalytical platforms were evaluated to optimize sensitivity and enable detection of recombinant human GDF11 in biological matrices; ELISA, Meso Scale Discovery, Gyrolab xP Workstation and Simoa HD-1.Results & methodology: After completion of custom assay development, the single-molecule ELISA (Simoa) achieved the greatest sensitivity with a lower limit of quantitation of 0.1 ng/ml, an improvement of 100-fold over the next sensitive platform (MSD).Discussion & conclusion: This improvement was essential to enable detection of GDF11 in biological samples, and without the technology the sensitivity achieved on the other platforms would not have been sufficient. Other factors such as ease of use, cost, assay time and automation capability can also be considered when developing custom immunoassays, based on the requirements of the bioanalyst.